2018
DOI: 10.1002/ejoc.201800900
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Linked meso‐BODIPYnyl Dithiahomoporphyrins: Synthesis and Properties

Abstract: A series of novel covalently linked meso‐BODIPYnyl dithiahomoporphyrins was synthesized by treating readily available tetrapyrrane and appropriate formyl BODIPY derivatives in the presence of catalytic amount of BF3·OEt2 in CH2Cl2 followed by oxidation using DDQ. The meso‐BODIPYnyl dithiahomoporphyrins were characterized by HR‐MS, 1D, 2D NMR and absorption spectroscopy, cyclic voltammetry and DFT studies. The spectral and electrochemical studies suggest that the BODIPY and homoporphyrin units in meso‐BODIPYnyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…exhibits novel physico-chemical properties. [5,6,8,[19][20][21][22] Another interesting modification of por-erocycle. The NMR studies indicated that the macrocycles were nonaromatic in nature and absorption spectra of 2,6-pyrihexaphyrins 2-6 showed one broad absorption band in the region of 600-1000 nm and two relatively sharp bands in the region of 350-500 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exhibits novel physico-chemical properties. [5,6,8,[19][20][21][22] Another interesting modification of por-erocycle. The NMR studies indicated that the macrocycles were nonaromatic in nature and absorption spectra of 2,6-pyrihexaphyrins 2-6 showed one broad absorption band in the region of 600-1000 nm and two relatively sharp bands in the region of 350-500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The core‐modified expanded porphyrins resulted by replacement of one or more pyrrole ring(s) with other five membered heterocycles such as thiophene, furan, selenophene, tellurophene, etc. exhibits novel physico‐chemical properties , , , . Another interesting modification of porphyrins/expanded porphyrins is to replace one or more five membered pyrrole rings with six membered heterocycles such as pyridine and the resulted pyridine containing porphyrinoids or pyriporphyrinoids would be expected to possesses unusual and different properties from regular pyrrole containing porphyrinoids , .…”
Section: Introductionmentioning
confidence: 99%
“…The homoporphyrins synthesized by researchers in 1967–1979 were found to be extremely unstable and decomposed even at 0 °C. , The instability of the homoporphyrins was mainly attributed to their nonaromatic nature. , However, in later years, it was shown that nonaromatic expanded porphyrinoids with [24], [28], , [32], [36], , [40], , [48], , and [64] , π-electron systems are extremely stable and exhibit very interesting physicochemical properties. Recently, we reported the synthesis of stable core-modified homoporphyrins in which two thiophene or two furan rings were introduced in place of the two pyrrole rings, which we called dioxahomoporphyrins 2 , and dithiahomoporphyrins 3 (Chart ), respectively. These dioxahomoporphyrins 2 or dithiahomoporphyrins 3 were synthesized by condensing the corresponding difuranethenediol or dithiopheneethenediol , with the appropriate meso -aryldipyrromethane under mild acid-catalyzed macrocycle-forming conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the synthesis of stable core-modified homoporphyrins in which two thiophene or two furan rings were introduced in place of the two pyrrole rings, which we called dioxahomoporphyrins 2 , and dithiahomoporphyrins 3 (Chart ), respectively. These dioxahomoporphyrins 2 or dithiahomoporphyrins 3 were synthesized by condensing the corresponding difuranethenediol or dithiopheneethenediol , with the appropriate meso -aryldipyrromethane under mild acid-catalyzed macrocycle-forming conditions. We explored the coordination chemistry of core-modified homoporphyrins 2 and 3 , but these macrocycles were found to show less tendency to form metal complexes. However, our studies showed that dithiahomoporphyrins 3 can act as a specific Hg 2+ ion sensor, as confirmed by various spectroscopic techniques, but our attempts to isolate a Hg 2+ complex of dithiahomoporphyrins 3 were unsuccessful .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation